Synthesis of Neem-Oil-Infused Niosome and Starch Nanoparticle Coatings for Preserving the Quality of Strawberry Fruit - Rahul Islam Barbhuiya; Charles Wroblewski; Sivaranjani Palanisamy Ravikumar; Jayasankar Subramanian; Abdallah Elsayed; Ashutosh Singh (Foods)
Strawberries face marketing challenges due to their short post-harvest shelf-life, largely impacted by shrivelling, weight loss, fungal decay, and mechanical damage. Neem oil (NO) is known for its shelf-life extension benefits; however, encapsulation is needed to maintain its efficacy. This study aimed to stabilize and encapsulate NO in a polymeric and lipid material to preserve the quality of strawberries stored at 4 ± 1 °C, 80 ± 2% RH for seven days. After seven days, the nanoparticle-coated fruits showed a weight loss of around 5.9% with niosomes and 8.9% with starch nanoparticles, while the control had a significant 32.45% weight loss. Additionally, both nanoparticle coatings significantly (p < 0.05) preserved fruit colour compared to the untreated control. The findings suggest that nanoparticle coatings could serve as an active agent in preserving the quality of strawberries within the food supply chain. The study provides valuable insights into post-harvest management and fruit preservation, showcasing the effectiveness of these coatings as active packaging solutions.